Water Quality Science, Assessments and Policy - Summers, Kevin (IntechOpen, 2020)
Water Quality - Science, Assessments and Policy examines many of the scientific issues; national, regional and local assessment practices and results; and national policy issues related to water quality. Chapters focus on three areas: water quality parameters, water quality treatments, and water quality assessments. This book provides a basic understanding of water quality issues and practical examples of their solution.